INOVASI BUDAYA DALAM DUNIA PENDIDIKAN - Hadaniah; Sri Wahyuni Juika; Nur Atia; Septiana Anugrah. S; Hasruddin Nur (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The development of digital technology has brought significant changes to education, particularly in learning culture, the role of educators, and educational systems. This article aims to examine cultural innovation in education through a literature review approach. The study employs a descriptive qualitative literature review by analyzing journal articles, conference proceedings, and educational policy documents published over the last ten years. The findings indicate that cultural innovation in education involves three main aspects: the transformation of teachers’ roles, curriculum adaptation to the digital era, and the use of technology to create inclusive, interactive, and collaborative learning environments. Although digital learning has great potential to improve effectiveness, accessibility, and the development of 21st-century skills, its implementation in Indonesia still faces challenges such as infrastructure disparities, low digital literacy, and conservative attitudes among some educators and educational institutions. Therefore, cultural innovation in education needs to be supported by sustainable policies, enhanced teacher professionalism, and equitable access to technology to improve the quality and competitiveness of national education in the era of globalization Keywords: cultural innovation, digital education, digital learning, teacher roles, educational transformation.